Impact of human papillomavirus vaccine on cervical cancer epidemic: Evidence from the surveillance, epidemiology, and end results program - Pei, Jiao; Shu, Ting; Wu, Chenyao; Li, Mandi; Xu, Minghan; Jiang, Min; Zhu, Cairong (Frontiers in Public Health, 2023)
Since 2006, the human papillomavirus (HPV) vaccine has been recommended for females aged 9–26 years in the United States. Aiming to evaluate the early effect of the HPV vaccine on cervical cancer, this study assessed the incidence of cervical cancer by age and histology before and after the introduction of HPV vaccination. Data on cervical cancer incidence from 1975–2019 were extracted from the Surveillance, Epidemiology, and End Results Program. Joinpoint regression was used to determine temporal trends over time. Future cervical cancer incidence (2015–2039) was projected using Bayesian age-period-cohort analysis. Age-period-cohort (APC) models were created to evaluate age, period, and cohort effects. For overall cervical cancer and cervical squamous cell carcinoma (SCC), incidence rate showed decreasing trends (-0.7%, and -1.0% annually, respectively), whereas cervical adenocarcinoma (AC) incidence continuously increased (2.6% annually). The incidence trends for AC were stable in the 20–24 and 25–29-year age groups, whereas there was an increasing trend in older age groups. Similarly, the projected trend for AC in females aged 20–30 years exhibited a decline, whereas an increase was predicted in the 31–40-year age group, especially in the 35–44 year age group. The birth cohort and period effects in SCC and AC were extracted from APC models. During the period of 1975–2019, the incidence of cervical AC remained almost unchanged in the age groups receiving HPV vaccines while increased in the age groups not receiving HPV vaccines. The birth cohort effects of SCC and AC of the cervix provided evidence supporting the effectiveness of the HPV vaccine in preventing cervical cancer.